Structural and biophysical characterization of cajanus cajan protease inhibitor - Shamsi, ToobaNaz; Parveen, Romana; Ahamad, Shahzaib; Fatima, Sadaf (Journal of natural science, biology and medicine, 2017)
A large number of studies have proven that Protease inhibitors (PIs), specifically serine protease inhibitors, show immense divergence in regulation of proteolysis by targeting their specific proteases and hence, they play a key role in healthcare. We aimed to access anticancer potential of PI from (CCPI). Also, crystallization of CCPI was targetted alongwith structure determination and its structure-function relationship. CCPI was purified from seeds by chromatographic techniques. The purity and molecular mass was determined by SDS-PAGE. Anticancer potential of CCPI was determined by MTT assay in normal HEK and cancerous A549 cells. The crystallization screening of CCPI was performed by commercially available screens. CCPI sequence was subject to BLASTp with homologous PIs. Progressive multiple alignment was performed using clustalw2 and was modelled using protocol of I-TASSER. The results showed ~14kDa CCPI was purified in homogeneity. Also, CCPI showed low cytotoxic effects of in HEK i.e., 27% as compared with 51% cytotoxicity in A549 cells. CCPI crystallized at 16°C using 15% PEG 6000 in 0.1M potassium phosphate buffer (pH 6.0) in 2-3weeks as rod or needles visualized as clusters under the microscope. The molecular modelling revealed that it contains 3 beta sheets, 3 beta hairpins, 2 β-bulges, 6 strands, 3 helices, 1helix-helix interaction, 41 β-turns and 27 γ-turns. The results indicate that CCPI may help to treat cancer aswell. Also, this is the first report on preliminary crystallization and structural studies of CCPI.